Asymptomatic plasmodial infection in pregnant women : A global scenario (2017)
ABSTARCT: Though asymptomatic plasmodial infection (API) is well known phenomenon and play an important role in different populations and malaria transmission settings, it has received less attention in malaria intervention strategies. This review was aimed to estimate the prevalence of API in pregnant women across the world. The bibliography records relevant to the study were searched on PubMed and Lilacs, till August 15, 2016, without restriction of language. A total of 78 references were identified, of which 29 met the inclusion criteria. The study of the identified reports revealed that the mean prevalence of API in pregnant women was 10.8% (3382/31186), with wide variation among countries and transmission settings. The reports showed that APIs are very common even in low malaria transmission areas, and most of the APIs are due to submicroscopic plasmodial infection (SPI). More sensitive diagnostic tools are required to address API and SPI in such areas. Every malaria endemic region/country should carry out systematic studies for accurate estimation of frequency for both these events (API and SPI) in different populations for planning appropriate intervention measures. Key words: Asymptomatic plasmodial infection; malaria; Plasmodium; pregnancy; submicroscopic plasmodial infection